Factors Related to the Development of CMV‐Specific CD8+ T cell Response in CMV‐Seropositive Solid Organ Transplant Candidates. Issue 3 (3rd February 2015) - Cantisán, S.; Rodelo‐Haad, C.; Páez‐Vega, A.; Nieto, A.; Vaquero, J. M.; Poyato, A.; Montejo, M.; Fariñas, M. C.; Rivero, A.; Solana, R.; Martín‐Malo, A.; Torre‐Cisneros, J.
<x xml:space="preserve">Abstract</x> This cross‐sectional study analyzes factors associated with the development of CMV‐specific CD8+ response, measured by IFNg production after cytomegalovirus (CMV) peptide stimulation, in CMV‐seropositive solid organ transplantation candidates. A total of 114 candidates were enrolled, of whom 22.8% (26/114) were nonreactive (IFNγ < 0.2 IU/mL). Multivariate logistic regression analysis showed that age, HLA alleles and organ to be transplanted were associated with developing CMV‐specific CD8+ immunity (reactive; IFNγ ≥ 0.2 IU/mL). The probability of being reactive was higher in candidates over 50 than in those under 50 (OR 6.33, 95%CI 1.93–20.74). Candidates with HLA‐A1 and/or HLA‐A2 alleles had a higher probability of being reactive than those with non‐HLA‐A1/non‐HLA‐A2 alleles (OR 10.97, 95%CI 3.36–35.83). Renal candidates had a higher probability of being reactive than lung (adjusted OR 8.85, 95%CI 2.24–34.92) and liver candidates (OR 4.87, 95%CI 1.12–21.19). The AUC of this model was 0.84 (p < 0.001). Positive and negative predictive values were 84.8% and 76.9%, respectively. In renal candidates longer dialysis was associated with an increased frequency of reactive individuals (p = 0.040). Therefore, although the assessment of CMV‐specific CD8+ response is recommended in all R+ candidates, it is essential in those with a lower probability of being reactive, such as non‐renal candidates, candidates under 50 or those with non‐HLA‐A1/non‐HLA‐A2 alleles.